The Boys of Winter : Life and Death in the U.S. Ski Troops During the Second World War - Sanders, Charles J. (Charles Jeffrey), 1958- (Book collections on Project MUSE., 2005)
"Drawing on dozens of interviews and extensive historical research, Charles J. Sanders reveals the stories of these young men. Sanders traces their journeys from childhood to ski championships and from training at Mount Rainier and in the Colorado Rockies to bloody battles against the Nazis in the Apennine Mountains of Northern Italy." "Ultimately, The Boys of Winter is the story of how some of America's best and brightest died in the war's last and most desperate battles under General Mark Clark, calling into question the necessity of their sacrifices - and those of thousands of other troops - on the "forgotten" Italian front in the spring of 1945"--Jacket.